Online on-demand delivery services of food and alcohol: A scoping review of public health impacts - Cassian Duthie; Tessa Pocock; Angela Curl; Elinor Clark; Dru Norriss; Susan Bidwell; Christina McKerchar; Rose Crossin (Elsevier, 2023)
The increase in availability of online on-demand food and alcohol delivery services has changed the way unhealthy commodities are accessed and understood. We conducted a systematic scoping review of academic and grey literature to map the current knowledge of public health and regulatory/policy outcomes arising from on-demand food and alcohol delivery (defined as delivery within 2 h). We systematically searched three electronic databases and completed supplementary forward citation searches and Google Scholar searches. In total, we screened 761 records (de-duplicated) and synthesised findings from 40 studies by commodity types (on-demand food or alcohol) and outcome focus (outlet, consumer, environmental, labour). Outlet-focused outcomes were most common (n = 16 studies), followed by consumer (n = 11), environmental (n = 7), and labour-focused (n = 6) outcomes. Despite geographical and methodological diversity of studies, results indicate that on-demand delivery services market unhealthy and discretionary foods, with disadvantaged communities having reduced access to healthy commodities. Services that deliver alcohol on-demand can also subvert current alcohol access restrictions, particularly through poor age verification processes. Underpinning these public health impacts is the multi-layered nature of on-demand services and context of the COVID-19 pandemic, which creates ongoing complications as to how populations access food and alcohol. Changing access to unhealthy commodities is an emerging issue in public health. Our scoping review considers priority areas for future research to better inform policy decisions. Current regulation of food and alcohol may not appropriately cover emerging on-demand technologies, necessitating a review of policy.